Home Quarantine Induced Health Anxiety During the Beginning of the COVID-19 Pandemic – Evidence From Iraq. (26th July 2023) - Taha, Perjan Hashim
Abstract: Objective: This study aimed to assess the compliance to voluntary home quarantine and to examine the prevalence and associated factors of health anxiety among the voluntary home quarantined population during the onset of the coronavirus disease (COVID-19) pandemic. Methods: An online survey questionnaire, including the health anxiety questionnaire, was administered to 1578 eligible adults from the general population of 19 governorates of Iraq. Results: Self-reported compliance with home confinement was reported by a majority of respondents (83%) and was followed to a larger extent by young adults (62.2%), females (53.9%), unmarried individuals (56.7%), university graduates (54.5%), unemployed individuals (48.6%), and inhabitants of the northern provinces (50.2%). Compliance was significantly correlated to the level of personal knowledge on COVID-19. The quarantined individuals experienced greater health anxieties and preoccupations and exhibited increased reassurance-seeking behavior. Higher knowledge of COVID-19 was a protective factor against health anxiety. Conclusions: A significant mental health burden is discovered among Iraqis during the quarantine period. Based on the insights gleaned from this study, psychological education and interventions should be prioritized to diminish the psychological impact of the quarantine experience, especially among the high-risk groups. Improvement in compliance to quarantine can be approached by providing better information regarding the novel infection.